Enhanced production of Th1- and Th2-type antibodies and induction of regulatory T cells in mice by oral administration of Cyclopia extracts with similar phenolic composition to honeybush herbal tea. (January 2020) - Yoshida, Tadashi; Malherbe, Christiaan J.; Okon, Kazunobu; Miura, Yutaka; Hattori, Makoto; Matsuda, Hiroshi; Muller, Christo J.F.; Joubert, Elizabeth
Graphical abstract: Highlights: Oral ingestion of Cyclopia extracts resulted in immunomodulatory activity in mice. Cyclopia extracts enhanced systemic humoral immune responses. Cyclopia extracts induced regulatory T cells. Effective mouse dose translated to HED of ca 300 mL herbal tea/day. Abstract: Immune-regulating activity of Cyclopia subternata and C. genistoides extracts (honeybush tea) in vitro, using a murine cell culture, merited investigation of their immune-regulating functions in vivo . Oral administration of the extracts and ovalbumin (OVA) to OVA specific-T cell receptor transgenic mice (DO11.10) significantly (P < 0.05) enhanced both Th1- and Th2-type antibody productions in the sera and generation of regulatory T cells (Treg cells) in the spleen. Demonstration of these activities in vivo confirmed those observed in vitro, suggesting that the active substances in honeybush extracts directly affected immune cells after absorption from the intestine. We demonstrated that the induced Treg cells from mice treated with C. subternata extract suppressed responses of antigen-stimulated naïve T cells when co-cultured, showing a comparable activity to naïve Treg cells. Exhibition of both immune-stimulatory and immune-regulatory activities by Cyclopia extracts in vivo supports growing consumption of Cyclopia spp. as herbal tea that can impact positively on health through the diet.